Integration of Self-Actualization and Self-Efficacy in the Formation of Islamic Character in Islamic Boarding Schools - Ali Idrus; Supian; KA. Rahman; Yudo Handoko (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study aims to determine the effect of self-actualization orientation and self-efficacy on the formation of Islamic character at the Al Hidayah Islamic Boarding School in Jambi City. Using a mixed method approach, data were collected from 140 students through structured questionnaires and interviews. Data analysis used descriptive statistics, correlation analysis, and multiple linear regression analysis. The results of this study indicate that there is a self-actualization orientation (r = 0.75, p < 0.001) and self-efficacy (r = 0.68, p < 0.001) that provide the most significant contribution to the development of Islamic character. In addition, high-quality educational services (r = 0.80, p < 0.001) play an important role in this process. These findings can provide valuable insights that are useful for improving Islamic education policies by emphasizing a holistic approach that integrates various aspects of development and a supportive learning environment. The limitations of this study include a cross-sectional design and a specific sample, which indicates the need for further research in various educational background sectors.